A participação do poder legislativo na definição das metas e prioridades do orçamento publico federal no periodo 1990/95 - Sucupira, João Antonio Silveira Lins (1996)
The development of the public budget is one of the most important responsibilities of the Legislative body in countries with a democratic framework, even though the initial stages of the budgetary laws have been progressively transferred to the Executive. Presently, the roles played by the Executive and Legislative bodies in the creation of the budget are defined in the various constitutions, when there can be observed a tendency towards balance between these two branches. The history of budgeting is closely associated with the growing power of the Legislative houses which demanded the right to authorize the collection of revenues and the outflow of public expenditures. The budget, first introduced in England as a form of political control of the Legislative body over the crown, was adopted by the French and the Americans in their struggles for liberty; and soon therefater it was implemented in most countries. In Brazil, using the various constitutions throughout its history as a reference, the participation of the Legislative branch in the development of the budget can be characterized by periods of greater or lesser control over budgetary decisions. The Federal Constitution of 1 988 reinstated the prerrogatives of the National Congress to make budgetary decisions that had been stripped from the Constitution in 1967. The Constitution brought important changes in this area, among them the conclusion of the process of the budgetary unification, the Legislative passage of not only the budgetary law but also new instruments of planning (the law of the multi-annual plan and the law of budgetary directives), the institution of a permanent bicameral commission made up of senators and representatives, and the possibility of amending the projects of the Executive branch. The law of budgetary directives, considered one of the most relevant innovations introduced into the section of the Constitution that deals with the public budget, was conceived with the larger objective of granting the Legislative branch a greater intervention in the elaboration of the budgetary law, anticipating the decisions that would be made regarding the goals and priorities to be achieved in the budgetary processo Despite the new instruments that widened the scope of the legislative's power, in the period from 1990 to 1995 this branch did not achieve its full potential in the definition of the budgetary agenda due to the lack of political will to pass the Complementary Law of Public Finances and the inability to achieve the desired structure and function outlined in the Constitution for the bi-cameral budgetary commission. The Legislative involvement in the budget was also hampered by the inexistence of governmental planning and by the deficiency of projects proposed by the Executive, which gave little attention to goals and priorities to be considered in the development of the annual.